Disaster Communication Governance at Yogyakarta International Airport - Achmad Rizki Arrajabi; Maulina Pia Wulandari; Yuyun Agus Riani (FAKULTAS DAKWAH UIN SALATIGA, 2026)
Public relations in high-risk infrastructure is not limited to media relations or message dissemination, but also includes stakeholder coordination, meaning alignment, and public trust maintenance during a crisis. This study reframes airport disaster communication as a strategic public relations practice by examining how stakeholder coordination is designed, enacted, and strengthened at Yogyakarta International Airport. Using a qualitative case study approach, data were collected through in-depth interviews, limited observation, and strategic document analysis involving airport authorities, operational units, and disaster-related external stakeholders. Guided by Stakeholder Management Theory and a strategic public relations perspective, the findings show that crisis coordination emerges through negotiated authority, layered information flows, frontline empathetic communication, and simulation-based institutional learning. Formal documents such as standard operating procedures and disaster management plans provide a basic structure, yet their effectiveness depends on cross-unit information synchronization and the capacity to translate technical risk into credible public messages. The study contributes to public relations scholarship by demonstrating that crisis communication in critical infrastructure functions as communicative governance that links stakeholder engagement, organization-public relationships, legitimacy, and adaptive resilience.